2017
DOI: 10.1002/ana.25028
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of LIMK‐1/cofilin‐1 pathway: A possible basis for alteration of neuronal morphology in experimental cerebral malaria

Abstract: Overall, our findings suggest that the altered neuronal morphology and dysregulation of LIMK-1/cofilin-1 pathway could affect the cognitive outcome after experimental CM. Therefore, this study could help to establish newer therapeutic strategies addressing long-term cognitive impairment after CM. Ann Neurol 2017;82:429-443.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…As SD induced memory impairment and anxiety were confirmed, SD mice were subjected to Golgi staining as described previously [ 40 ]. Mice were anesthetized with pentobarbital sodium and brains were removed.…”
Section: Methodsmentioning
confidence: 99%
“…As SD induced memory impairment and anxiety were confirmed, SD mice were subjected to Golgi staining as described previously [ 40 ]. Mice were anesthetized with pentobarbital sodium and brains were removed.…”
Section: Methodsmentioning
confidence: 99%
“…In general, disruption of the blood–brain barrier, subsequent infiltration of immune cells, and hemorrhage are known to comprise a critical mechanism of CM that can cause nerve tissue damage [ 4 ]. Previous research has shown that neuronal damage can lead to neurological sequelae in children with CM and mice with experimental cerebral malaria (ECM) [ 5 7 ], but the underlying mechanism remains unclear. Recently, significantly increased levels of oxidative stress were detected in patients with severe malaria, including those with CM [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PPARγ has shown neuroprotective effects via various pathways and promotes neuronal repair, making it an attractive adjuvant therapy. Dysregulation of the limk-1/cofilin-1 pathway might lead to alterations in neuronal morphology and is considered the cause of cognitive defects in patients surviving CM ( Simhadri et al., 2017 ); therefore, the LIMK-1/cofilin-1 pathway is considered a potential therapeutic target for CM. In addition, granzyme-B produced by CD8 + T cells directly kills neurons through cytotoxic function and activation of caspase-3 and calpain1 ( Kaminski et al., 2019 ).…”
Section: Treatmentmentioning
confidence: 99%